'Malaysia’ An Inevitable Creation, 16 September 1963 - Ooi, Keat Gin (Universiti Sains Malaysia, 2017)
The concept of 'Malaysia' was conceived as a strategy of the westem powers notably Britain, to ensure that its former colonial possessions, namely (British) Malaya and (British) Bomeo (sarawak, Brunei, North Bomeo) did not switch or fall into the socialist/ communist camp. The genesis of the formation of the Federation of Malaysia which comprised the Federation of Malaya, Singapore, Sarawak, Sabah (formerly North Borneo), and that was realized on 16 September 1963 presented a bulwark to the advancement of the influence of the communist ideology in the Southeast Asia region.The post-war situation and condition of the then British colonial territories and protectorates of Malaya, Singapore, sarawak, Brunei, and North Borneo witnessed the increasing influence and threat of communism permeating the region. comparatively, however, Brunei and North Borneo had scant Leftist impact.